Prescription pattern of antibiotics in respiratory disorders in a tertiary care teaching hospital in Eastern part of India - Gupta, Chandra Narayan; Chatterjee, Kripasindhu (International Journal of Research in Medical Sciences, 2017)
Background: Respiratory infections are increasing globally with parallel increase in world population, pollution, urbanization, overcrowding, global warming and poverty. Multi drug resistant virulent bacteria are growing very rapidly. The objective of this study was to know the prescribing pattern of antibiotics in hospitalized patients suffering from different common respiratory disorders. Methods: This was a retrospective and observational study. Data was captured from 1st January 2016 to 31st December 2016 at ICARE Institute of Medical Sciences and Research and Dr. B.C.Roy Hospital. Total 200 patients were taken for the study of age range from 10 to 50 years. Results: COPD, bronchial asthma, pneumonia and ARIs were the most frequent respiratory illnesses among patients attended Medicine OPD. Most common antibiotics prescribed were co-amoxyclav, ceftriaxone, moxifloxacin, clarithromycin, azithromycin and aminoglycosides. Conclusions: Injudicious use of antibiotics in trivial viral respiratory infections may give rise to antibiotic resistant strains in the community.